Opening the door on entry inhibitors in HIV: Redefining the use of entry inhibitors in heavily treatment experienced and treatment‐limited individuals living with HIV. Issue 9 (16th March 2022) - Orkin, Chloe; Cahn, Pedro; Castagna, Antonella; Emu, Brinda; Harrigan, P Richard; Kuritzkes, Daniel R.; Nelson, Mark; Schapiro, Jonathan
Abstract: Introduction: Entry inhibitors are a relatively new class of antiretroviral therapy and are typically indicated in heavily treatment experienced individuals living with HIV. Despite this, there is no formal definition of 'heavily treatment experienced'. Interpretation of this term generally includes acknowledgement of multidrug resistance and reflects the fact that patients in need of further treatment options may have experienced multiple lines of therapy. However, it fails to recognize treatment limiting factors including contraindications, age‐associated comorbidities, and difficulty adhering to regimens. Methods: This manuscript follows a roundtable discussion and aims to identify the unmet needs of those living with HIV who are in need of further treatment options, to broaden the definition of heavily treatment experienced and to clarify the use of newer agents, with an emphasis on the potential role of entry inhibitors, in this population. Results/Conclusions: Within the entry inhibitor class, mechanisms of action differ between agents; resistance to one subclass does not confer resistance to others. Combinations of entry inhibitors should be considered in the same regimen, and if lack of response is seen to one entry inhibitor another can be tried. When selecting an entry inhibitor, physicians should account for patient preferences and needs as well as agent‐specific clinical characteristics. Absence of documented multidrug resistance should not exclude an individual from treatment with an entry inhibitor; entry inhibitors are a valuable treatment option for all individuals who are treatment limited or treatment exhausted. We should advocate for additional clinical trials that help define the role of entry inhibitors in people with exhausted/limited ART options other than drug resistance.